2008
DOI: 10.1016/j.watres.2007.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Functional variability of dissolved organic matter from the surface water of a productive lake

Abstract: River Fulvic Acid was used as a quality control standard. For 9 of the assays, variability among DOM samples was significantly (p<0.01) greater than could be explained by analytical error. Seasonal trends observed for 6 of the assays could be explained by a simple mixing model in which the two end-members were DOM from the catchment (allochthonous) and DOM produced within the lake (autochthonous). The fraction of autochthonous DOM predicted by the model is significantly correlated (p <0.01) with chlorophyll co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…Overall, the water binding capacity of both rivers with respect to all examined HM was higher in summer. The obtained results are in good agreement with data of [11,14], according to which DOM production within water body increases in summer because of plankton growth. Moreover, the greater surface runoff in spring and summer leads to an increase in the concentration of allochthonous DOM, which can also contribute largely to metal bioavailability.…”
Section: Resultssupporting
confidence: 88%
“…Overall, the water binding capacity of both rivers with respect to all examined HM was higher in summer. The obtained results are in good agreement with data of [11,14], according to which DOM production within water body increases in summer because of plankton growth. Moreover, the greater surface runoff in spring and summer leads to an increase in the concentration of allochthonous DOM, which can also contribute largely to metal bioavailability.…”
Section: Resultssupporting
confidence: 88%
“…Although simple absorption and fluorescence DOM quality parameters have frequently been used in the past to characterize natural DOM (Gondar et al 2008;Green and Blough 1994), they are not always the best tools to employ. For example, absorbance measurements are subject to interferences from particles and inorganic species such as iron and nitrate (Weishaar et al 2003), these interferences being more important at low [DOC] than at high [DOC] situations (Green and Blough 1994;.…”
Section: Parafacmentioning
confidence: 99%
“…Optical properties of DOM that have been used to distinguish between the types of DOM include absorbance (Gondar et al 2008;Weishaar et al 2003) and fluorescence (Coble 1996;McKnight et al 2001;Stedmon and Markager 2005). Absorbance and fluorescence spectroscopy are particularly useful tools in the analysis of DOM quality, in that they are relatively simple, rapid, sensitive, and non-destructive.…”
Section: Introductionmentioning
confidence: 99%
“…This production is a critical link in the microbial loop of aquatic ecosystems. In a lake system that experiences a wide range of Chl a concentrations, Gondar et al (2008) report that concentrations of autochthonous DOM are significantly correlated with Chl a concentrations (a proxy for primary production by phytoplankton). Likewise, in the Arctic Ocean, Davis and Benner (2007) have shown that there is a strong seasonal link between primary productivity and the production of labile DOM.…”
Section: Conservative and Reactive Transport Modeling Of Dom-mentioning
confidence: 99%